Bis(perchlorocatecholato)silane and heteroleptic bidonors: hidden frustrated Lewis pairs resulting from ring strain - Hartmann, Deborah; Braner, Sven; Greb, Lutz (Chemical communications, 2021)
Bis(perchlorocatecholato)silane and bidentate N,N- or N,P-heteroleptic donors were reacted to form hexacoordinated complexes. Depending on the ring strain and hemilability in the adducts, frustrated Lewis pair (FLP) reactivity with aldehydes and catalytic ammonia borane dehydrocoupling was enabled. All reactions were analyzed using density functional theory. This approach represents an alternative way, beyond relying on steric bulk, to achieve frustration in bimolecular FLPs.
Gesehen am 05.10.2022